Human Rights Aspect in the Indonesian Energy Transition: the Challenges of Promoting the Right to a Clean, Healthy and Sustainable Environment - Nur, Asrul Ibrahim (Serikat Pengajar Hak Asasi Manusia Indonesia, 2022)
This article critically examines how Indonesia’s legal framework for energy transition integrates human rights, particularly the right to a clean, healthy, and sustainable environment. As a Global South country balancing climate goals with socio-economic development, Indonesia is legally bound both constitutionally and internationally to pursue a just and inclusive energy transition. While prior studies often treat environmental rights and climate governance as distinct areas, this article contributes to a growing body of scholarship that bridges human rights law and energy governance in postcolonial contexts. It offers one of the first systematic legal analyses of how Indonesia’s energy laws support or fall short of its environmental rights obligations. Using a doctrinal legal research methodology, the study combines statutory and conceptual analysis to assess coherence and effectiveness in national energy legislation. It identifies three major challenges: institutional fragmentation, conflicting legal instruments, and structural fossil fuel dependence. These barriers hinder the realisation of environmental rights and expose tensions between economic imperatives and human rights commitments. The article advances the academic conversation by foregrounding climate justice and rights-based legal reform as essential for sustainable transition pathways in the Global South. It argues that without embedding human rights principles into energy law and policy, Indonesia risks perpetuating exclusion and inequality. The study calls for harmonised legislation, institutional coordination, and a rights-based approach to align the energy transition with both constitutional duties and global human rights norms.